2017
DOI: 10.1002/ece3.2986
|View full text |Cite
|
Sign up to set email alerts
|

Barcoding rotifer biodiversity in Mediterranean ponds using diapausing egg banks

Abstract: The biodiversity of Mediterranean freshwater bodies is among the most threatened worldwide; therefore, its accurate estimation is an urgent issue. However, traditional methods are likely to underestimate freshwater zooplankton biodiversity due to its high species seasonality and cryptic diversity. We test the value of applying DNA barcoding to diapausing egg banks, in combination with the creation of a reference collection of DNA barcodes using adult individual samples, to characterize rotifer communities. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 109 publications
1
10
0
Order By: Relevance
“…Thus increasing the number of putative species in B. quadridentatus. Only five sequences from the Iberian Peninsula reported by Moreno et al (2017) fell within mitochondrial lineage G of this study (see Fig. S5).…”
Section: Discussionmentioning
confidence: 75%
“…Thus increasing the number of putative species in B. quadridentatus. Only five sequences from the Iberian Peninsula reported by Moreno et al (2017) fell within mitochondrial lineage G of this study (see Fig. S5).…”
Section: Discussionmentioning
confidence: 75%
“…Such high genetic distances within the same morphospecies is known in rotifers for cases of cryptic or pseudocryptic species (e.g. Mills et al, 2017;Moreno et al, 2017). Indeed, the use of a statistical approach to identify taxonomic units from DNA sequence data, such as the ABGD method we applied, revealed that several cryptic taxa could be potentially present in our dataset.…”
Section: Abgdmentioning
confidence: 62%
“…They found that resting stages of several zooplankton species hatched from these cores, including P. similis which was one of most abundant zooplankters at certain times of year. Moreno et al reported that Proales sp. hatched from DEs collected from sediments of Tinaja Lake located in Ruidera Natural Park in Central Spain.…”
Section: Discussionmentioning
confidence: 99%